PERUBAHAN POLA PERGERAKAN MASYARAKAT SEBAGAI DAMPAK PENERAPAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI KOTA YOGYAKARTA - Yurdhi Mahalina; Isti Andini; Ana Hardiana (ARSITEKTURA, 2016)
The density of urban network occurs due to the society temporary relocation in a short distance. Yogyakarta is one of the cities that has a high network  density  with working as the most dominant society movement patterns. Yogyakarta now also implementing the concept of city development based on information and communication technology (ICT) as stated in Yogyakarta Cyber City since 2005. The application of ICT in Yogyakarta has been done in the administration sector (e-government) and several other society service, in which the application of ICT allows some changes in the pattern of society movement. The purpose of this research was to determine the impact of ICT application toward the changing patterns of society movement seen from the condition of before and after the use of ICT in accessing various social services sector. This research was conducted throughout 14 districts in Yogyakarta and also in several service sectors necesarry for the people. Methods applied to determine the changes of  society movement pattern as a result of ICT application was reviewed based on the variable of service sector performance, the level of ICT used by the public, the number of people’s destination of their respective service sector, and also the quantity of movement among society zones seen from the point of origin and the destination point. The result of the research proved that there are changes in the society movement patterns at the decline the network density indicated by the decline of the number of people’s destination and by the decrease in the network density path, and also the decrease in the movement quantity among society zones which proves the theory of movement decline from the suburbs area to urban area. The application of ICT in several service sectors has enabled people to access the service at anytime and anywhere easily. However, the application of ICT in Yogyakarta has limited human resources in operating the service, and this make the number of society movement can not be completely substituted by the application of ICT. Keywords: Cyber City, ICT Use, Movement Patterns, E-Government